The language of crisis metaphors, frames and discourses - Huang, Mimi; Holmgreen, Lise-Lotte (Discourse approaches to politics, society, and culture ;, 2020)
"In times of crisis, how do people conceptualise and communicate their experiences through different forms and channels? How can original research in cognitive linguistics, discourse analysis and crisis studies advance our understanding of the ways in which we interact with and communicate about crisis events? In answering these questions, this volume examines the unique functions, features and applications of the metaphors and frames that emerge from and give shape to crisis-related discourses. The chapters in this volume present original concepts, approaches, authentic data and findings of crisis discourses in a wide range of organisational, political and personal contexts that affect a diverse body of language users and communities. This book will appeal to a broad readership in linguistics, sociological studies, cognitive sciences, crisis studies as well as language and communication researchers and practitioners"--